A novel reliability technique for implementation of Performance-Based Seismic Design of structures. (1st July 2017) - Gaxiola-Camacho, J. Ramon; Azizsoltani, Hamoon; Villegas-Mercado, Francisco J.; Haldar, Achintya
Highlights: A unified Performance-Based Seismic Design (PBSD) procedure is proposed. A novel reliability analysis procedure is proposed for time domain dynamic loading. An improved response surface method is proposed. An Improved Sampling Scheme is proposed. The proposed procedure is successfully implemented for PBSD. Abstract: A unified Performance-Based Seismic Design (PBSD) procedure is proposed and successfully implemented. It provides an alternative to the currently used life safety design requirement. To successfully develop the concept, structures are represented by finite elements and excited by the seismic loading in time domain. A novel reliability evaluation procedure is proposed for such representation. An improved response surface based procedure is proposed by combining it with the First-Order Reliability Method (FORM) and the appropriate response surfaces are constructed by combining the saturated design and the central composite design sampling schemes. Performances are defined in terms of Collapse Prevention (CP), Life Safety (LS), and Immediate Occupancy (IO), as commonly used in the profession. The corresponding risks are evaluated by exciting a 9-story steel frame designed by experts satisfying all post-Northridge seismic design requirements. It was excited by 20 earthquake time histories for each performance level and the corresponding probabilities of failure were estimated. It took around 300 deterministic evaluations. The accuracy of the method was established using 600, 000 cycles of Monte Carlo simulations. The probabilities of failure estimated using the proposed algorithm are very similar to that of simulations indicating that it is accurate. The probability of failure for two serviceability limit states (overall and inter-story drifts) are very similar, indicating that the procedure will satisfy the basic intent of PBSD. They are also similar to the values used in developing the Load and Resistance Factor Design (LRFD) guidelines used in many current design codes. Designing a structure using multiple time histories, as suggested in recent design guidelines, is a step in the right direction. From the results and the observations made in this study, the authors believe that they proposed a robust, efficient, and accurate unified PBSD procedure and documented its implementation potential.